The Supreme Court : an analytic history of constitutional decision making / Tom S. Clark. - Clark, Thomas S., 1980- (Political economy of institutions and decisions., 2019)
This book presents a quantitative history of constitutional law in the United States and brings together humanistic and social-scientific approaches to studying law. Using theoretical models of adjudication, Tom S. Clark presents a statistical model of law and uses the model to document the historical development of constitutional law. Using sophisticated statistical methods and historical analysis of court decisions, the author documents how social and political forces shape the path of law. Spanning the history of constitutional law since Reconstruction, this book illustrates the way in which the law evolves with American life and argues that a social-scientific approach to the history of law illuminates connections across disparate areas of the law, connected by the social context in which the Constitution has been interpreted.